The Art of Neighbouring. Making Relations Across China's Borders - Zhang, Juan; Saxer, Martin (Amsterdam University Press, 2017)
'Rising China' - the nation, the notion, and the buzzword - sparks dreams and triggers fears. Borders that were closed during the Cold War era have again become zones of contact and exchange. At the same time, security concerns remain high, territorial disputes still loom large. In this context, engaging in everyday neighbouring relations has become a necessity for those living in these zones of contact and exchange. The experiences and realities of relation-making across China's borders shape life in profound and lasting ways.